Animal-based medicines: biological prospection and the sustainable use of zootherapeutic resources - Costa-Neto,Eraldo M. (2005)
Animals have been used as medicinal resources for the treatment and relieve of a myriad of illnesses and diseases in practically every human culture. Although considered by many as superstition, the pertinence of traditional medicine based on animals cannot be denied since they have been methodically tested by pharmaceutical companies as sources of drugs to the modern medical science. The phenomenon of zootherapy represents a strong evidence of the medicinal use of animal resources. Indeed, drug companies and agribusiness firms have been evaluating animals for decades without paying anything to the countries from where these genetic resources are found. The use of animals' body parts as folk medicines is relevant because it implies additional pressure over critical wild populations. It is argued that many animal species have been overexploited as sources of medicines for the traditional trade. Additionally, animal populations have become depleted or endangered as a result of their use as experimental subjects or animal models. Research on zootherapy should be compatible with the welfare of the medicinal animals, and the use of their by-products should be done in a sustainable way. It is discussed that sustainability is now required as the guiding principle for biological conservation.